2016
DOI: 10.1080/07347324.2016.1148494
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Treatment Outcomes Among Canadian Military and Civilian Substance Users Attending the Same Residential Treatment Program

Abstract: Substance use disorder is a concerning health issue, affecting military and civilians alike. Due to exceptional workplace demands and a unique military culture, it is important to explore whether military members respond to addiction treatment in the same manner as their civilian counterparts. The present study compared individual characteristics and addiction treatment outcomes between Canadian military members and civilians attending the same residential program. Results revealed that both groups experienced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…Gavrysh and colleagues examined a 30-to 80-day residential treatment program that included medical treatment, psychoeducation, group therapy, 12-step programs, and relapse prevention services, as well as such elements as meditation and physical exercise. They found that military veterans experienced a significant decrease in reported drinks per day and days using drugs in the six months following completion of the program (Gavrysh et al, 2016). Ilgen and colleagues conducted an observational study of a randomly selected sample of veterans from various inpatient, intensive outpatient, and outpatient treatment settings across the country.…”
Section: Multiple-component Interventionsmentioning
confidence: 99%
“…Gavrysh and colleagues examined a 30-to 80-day residential treatment program that included medical treatment, psychoeducation, group therapy, 12-step programs, and relapse prevention services, as well as such elements as meditation and physical exercise. They found that military veterans experienced a significant decrease in reported drinks per day and days using drugs in the six months following completion of the program (Gavrysh et al, 2016). Ilgen and colleagues conducted an observational study of a randomly selected sample of veterans from various inpatient, intensive outpatient, and outpatient treatment settings across the country.…”
Section: Multiple-component Interventionsmentioning
confidence: 99%